Stress Levels and Sleep Quality: A Study of Final-Year Nursing Students at ITSK RS dr. Soepraoen Malang - Maysa Faranadia Wulansari; Tien Aminah; Musthika Wida Mashitah (PROFESSIONAL HEALTH JOURNAL, 2026)
Stress is a psychological response that arises when an individual faces certain pressures or demands. One common form of stress experienced by university students is academic stress, particularly among final-year students who are completing their thesis as a graduation requirement. High academic demands often become a major source of stress that affects both physical and mental health, including sleep disturbances. This study aims to determine the relationship between stress levels and sleep quality among final-year Bachelor of Nursing students at ITSK RS dr. Soepraoen Malang. This research employed a quantitative correlational design with a cross-sectional approach. Sampling was conducted using a total sampling technique, resulting in 159 participants. Data were collected using the DASS-42 questionnaire to measure stress levels and the PSQI to assess sleep quality. Data analysis was performed using the Chi-Square test (p < 0.05). The results showed a p-value of 0.001, indicating a significant relationship between stress levels and sleep quality. Higher levels of stress were associated with poorer sleep quality. Therefore, it is recommended that the university provide mentoring or counseling programs to help students manage academic stress, especially for final-year students. Students are also encouraged to enhance positive coping strategies and manage their study time more effectively.